A taxonomic revision of Zamia montana and Zamia oligodonta, with notes on their conservation status - Calonje, Michael; Morales, Gustavo; López-Gallego, Cristina; Roldán, Francisco Javier (Phytotaxa, 2015)
The taxonomy of Zamia montana and Z. oligodonta, two poorly understood species occurring at high elevations in the Western Cordillera of Colombia, is discussed. Zamia oligodonta was recently synonymized under Z. montana, but information derived from recent field studies is provided showing the two species are quite distinct. A treatment of both species is presented, including discussion of the major morphological differences between them and also between other South American species with prominently-veined leaflets. The conservation status of both species is evaluated.